صلاحية الكتاب التعليمي على النظرية النفسية لتنمية مهارة الكلام لدي الطلاب فى المدرسة دار الأخوة الابتدائية لتحفيظ القرءان - Dian Ahmad jufrih; Mochamad Fawaidur Rochman; Uril Bahruddin (Nady Al-Adab : Jurnal Bahasa Arab, 2021)
الملخص من الجدير بالذكر، أن الكتاب التعليمي المطور على ضوء النظرية النفسية يؤثر على الطلبة اهتماما و دافعا كثيرا فى عملية التعليم حتي تحقق أهداف و أغراض تعليم اللغة العربية خاصة لتنمية مهارة القراءة. أما الأهداف فى هذا البحث 1) لوصف الكتاب التعليمي بالصور الملونة على النظرية النفسية لتنمية مهارة الكلام لدي الطلاب فى المدرسة دار الأخوة الإبتدائية لتحفيظ القرءان.2) لوصف صلاحية الكتاب التعليمي المنتج بالصور الملونة على النظرية النفسية 3) لوصف فعالية استخدام الكتاب التعليمي بالصور الملونة على النظرية النفسية. يستخدم الباحثون في هذا البحث المنهج الوصفي التقويمي. يهدف هذا البحث إلى وصف ظواهر أو أحداث أو أشياء ويهم أيضا بتقرير ماينبغي أن تكون عليه الأشياء والظواهر التي يتناولها البحث . وأما البايانات نوعان فهما النوعي والكمي. وأما أدوات البحث لجمع المعلومات فهي الملاحظة والإستبانة والإحتبار. ونتيجة صلاحية الكتاب التعليمي على النظرية النفسية لتنمية مهارة الكلام من خبير المحتويات فهي تبلغ إلى القيمة 90% أما نتيجة الصلاحية من خبير التصميم فهمي تبلغ إلى القيمة وكل النتيجة تدل على درجة لائق جدا باستخدام المواد التعليمية على النظرية النفسية لتنمية مهارة الكلام لدي الطلاب فى المدرسة دار الأخوة الإبتدائية لتحفيظ القرءان . اعتمادا على الجدول نتائج الاختبار التائي (T) معرفة أن قيمة T-Test هي 7.629 وأما قيمة T-Table هي 2,179 هذا دليل أن قيمة T-Test أكبر من T-Table. وهذا يدل على أن الكتاب التعليمي المطور على النظرية النفسية فعال لتنمية مهارة الكلام لدي الطلاب فى المدرسة دار الأخوة الإبتدائية لتحفيظ القرءان ". الكلمات المفتاحية: صلاحية، الكتاب التعليمي، النظرية النفسية. Abstract: It is worth mentioning that the educational book which was developed from the point of view of psychological theory attracted students' interest and great motivation in the learning process to achieve the goals and objectives of teaching Arabic, especially to develop reading skills. The purpose of this study 1) To describe the book "lughatina lughatu al-quran" with colorful pictures based on psychological theory to develop speaking skills of elementary school students Darul Ukhwah Li At-Tahfidz Al-Quran 2) To describe the validity of the book "lughatina lughatu al-quran" which color pictures based on psychological theory 3) Describe the effectiveness of using the book "Lughatina Lughatu Al-Quran" which has color pictures based on psychological theory. In this study, the researcher used a descriptive evaluative method. This study aims to describe phenomena, events or things, and is also concerned with deciding what things and phenomena should be covered by research. Data consists of two types, qualitative and quantitative. The research tools to collect information are observation, questionnaires, and experiments. The results of the validity of learning books based on psychological theory for the development of speaking skills from content experts reached a value of 90%, while the results of the validity of Fahmy's design experts reached a value of 98%, and all the results showed a very feasible level of using psychological theory educational materials to develop the speaking skills of students of this school. Darul Ukhwah Li At-Tahfidz Al-Quran elementary school. Based on the table of T-Test results, it is known that the T-Test value is 7.629 and the T-Table value is 2.179. Table. This shows that the educational book developed on psychological theory is effective for developing students' speaking skills at the Darul Ukhwah Li At-Tahfidz Al-Quran elementary school. Keywords: validity, textbooks, psychological theory